Censorship in Ukrainian Children’s Literature in Totalitarian and Post-Totalitarian Society - Kachak, Tetiana; Blyznyuk, Tetyana; Golod, Roman (Knygotyra, 2025)
This article contains an overview of the censorship of Ukrainian children’s literature of the 20th – 21st centuries, which is largely related to socio-political processes and the dominant ideology. Another factor of prohibitions is contradictions with the accepted social, religious or sexual norms, as well as the traditional stereotypes about the upbringing of young people.The outline of the scope of ideological censorship, under the pressure of which Ukrainian children’s literature found itself during the totalitarian Soviet regime from 1922 to 1990, is presented. It is noted that censorship bodies were set up in the USSR to ban certain works in order to prevent the spread of national ideas and/or information that contradicted the communist ideology and the Soviet propaganda. For decades, special instructions were issued for recommended reading for children and for removing ‘harmful literature’ from reading rooms, bookstores, and the market in general.Simultaneously, bans and manifestations of censorship in children’s literature since the restoration of Ukraine’s independence (from the 1990s to today) are analyzed. It is asserted that the situation changed with the beginning of the post-totalitarian period in the history of Ukraine. Ideological involvement disappeared, whereas topics of national history, culture and traditions developed. Gradually, there was a conditional removal of taboos on ‘difficult’ topics for children (death, illness, sexual experience, psychological problems, etc.). New and non-stereotypical patterns of child behavior emerged in literature. Various genres of children’s literature actively developed, and writers learned to talk to young readers about everything while using ‘their’ language. The ratio of utilitarian and artistic in texts for children has been changing in favor of the latter.
Keywords: Censorship; Ukrainian children's literature; totalitarian society; post-totalitarian society; ideology; ban on fairy tales